Relationship between insulin resistance and hypercortisolism: HAIR-AN syndrome mimicking cushing´s syndrome - Roxana P. Gómez-Ruiz; Miguel A. Gómez-Sámano (Revista Mexicana de Endocrinología, Metabolismo y Nutrición)
HAIR-AN syndrome, defined by hyperandrogenism, insulin resistance (IR), and acanthosis nigricans, is a rare subset of polycystic ovary syndrome characterized by more severe IR and an increased risk of metabolic complications. We present a case of a female in her early 20s with initially displayed signs of hypercortisolism – central obesity, hirsutism, and IR – symptoms that can overlap with Cushing´s syndrome. The coexistence of IR and hypercortisolism can make the diagnosis and management of these patients particularly challenging.